2015
DOI: 10.1063/1.4937400
|View full text |Cite
|
Sign up to set email alerts
|

Concentration, chemical bonding, and etching behavior of P and N at the SiO2/SiC(0001) interface

Abstract: Phosphorous and nitrogen are electrically active species at the SiO2/SiC interface in SiC MOSFETs. We compare the concentration, chemical bonding, and etching behavior of P and N at the SiO2/SiC(0001) interface using photoemission, ion scattering, and secondary ion mass spectrometry. Both interfacial P and N are found to be resistant to buffered HF solution etching at the SiO2/SiC(0001) interface while both are completely removed from the SiO2/Si interface. The medium energy ion scattering results of etched ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The trap passivation mechanism by phosphorus is only partially understood. It has been reported that, at the interface as well as in the bulk PSG layer, P is primarily bound to O atoms, which are themselves bonded to Si or C atoms [46]. This suggests that the trap passivation mechanism due to P may be related to re-arranging the critical interfacial dielectric layer, relieving interface stress and possibly allowing better passivation of the dangling bonds [46].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The trap passivation mechanism by phosphorus is only partially understood. It has been reported that, at the interface as well as in the bulk PSG layer, P is primarily bound to O atoms, which are themselves bonded to Si or C atoms [46]. This suggests that the trap passivation mechanism due to P may be related to re-arranging the critical interfacial dielectric layer, relieving interface stress and possibly allowing better passivation of the dangling bonds [46].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that, at the interface as well as in the bulk PSG layer, P is primarily bound to O atoms, which are themselves bonded to Si or C atoms [46]. This suggests that the trap passivation mechanism due to P may be related to re-arranging the critical interfacial dielectric layer, relieving interface stress and possibly allowing better passivation of the dangling bonds [46]. Accordingly, the effect of phosphorus on near-interface traps can be summarized by the following theories reported in the literature: (1) the P atoms act as a network former and result in reconstruction of the oxide network in SiO 2 (Si-Si bonds elimination) [26,28,46] (2) C related defects are removed by the P doping of SiO 2 [28,[47][48][49] where threefold carbon atoms at the interface are replaced by a P=O group [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen (N) acts as an n-type dopant in SiC, and after N 2 O annealing there may be some counter doping of the pdoped regions (created by aluminium dopants) by N [15,16] . These p regions are used underneath the Schottky contact in the termination region.…”
Section: Resultsmentioning
confidence: 99%
“…For example, this polarize charge can change a "normally-off" device to a "normally-on" device. X-ray photoelectron spectroscopy (XPS) results [34,35] reveal that PSG layers cannot be removed completely by etching in BOE if is grown on 4H-SiC while opposite is true for the layer grown on Si. After BOE etching in the case of SiC, a 2-3-nm Si-C-O-P interfacial layer can still be seen which is equivalent to a phosphorous areal density of 2 × 10 .…”
Section: Etched Psg Processmentioning
confidence: 99%